2009
DOI: 10.1680/stbu.2009.162.5.323
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening RC beam–column connections with FRP strips

Abstract: Reinforced concrete connections, designed prior to the implementation of earthquake design standards, may be vulnerable to shear failure during a seismic attack. Addition of externally bonded fibre-reinforced polymer (FRP) composites can enhance not just the shear capacity but the deformation and energy absorption capacity of the connection. The majority of research studies to date have opted for complete or near-complete coverage of the joint region with FRP and have subjected the test specimens to cyclic (pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 14 publications
(11 reference statements)
0
8
0
1
Order By: Relevance
“…A database of 171 experimental RC beam-column connections (98 exterior and 73 interior) was compiled from the published literature (Alva et al, 2007;Antonopoulos and Triantafillou, 2003;Attaalla, 2004;Au et al, 2005;Chalioris et al, 2008;Chun et al, 2009;Chutarat and Aboutaha, 2003;Clyde et al, 2000;Dhakal et al, 2005;Durrani and Wight, 1985;Ehsani and Alameddine, 1991;Ehsani and Wight, 1985;Ehsani et al, 1987;El-Amoury and Ghobarah, 2002;Fisher and Sezen, 2011;Ghobarah and El-Amoury, 2005;Said, 2001, 2002;Hwang et al, 2004Hwang et al, , 2005Ishibashi, 1993;Kaku and Asakusa, 1991;Sirkelis, 2005, 2008;Kitayama et al, 1991;Kuang and Wong, 2006;Le-Trung et al, 2010;Lee et al, 2010;Leon, 1990;Liu, 2006;Lu et al, 2012;Megget, 1974;Meinheit and Jirsa, 1977;Morita et al, 1999;Murty et al, 2003;Noguchi and Kashiwazaki, 1992;Noguchi and Kurusu, 1988;Oka and Shiohara, 1992;Otani et al, 1984;Pantelides et al, 2002;Park and Paulay, 1974;Shrestha et al, 2009;...…”
Section: Experimental Databasementioning
confidence: 99%
“…A database of 171 experimental RC beam-column connections (98 exterior and 73 interior) was compiled from the published literature (Alva et al, 2007;Antonopoulos and Triantafillou, 2003;Attaalla, 2004;Au et al, 2005;Chalioris et al, 2008;Chun et al, 2009;Chutarat and Aboutaha, 2003;Clyde et al, 2000;Dhakal et al, 2005;Durrani and Wight, 1985;Ehsani and Alameddine, 1991;Ehsani and Wight, 1985;Ehsani et al, 1987;El-Amoury and Ghobarah, 2002;Fisher and Sezen, 2011;Ghobarah and El-Amoury, 2005;Said, 2001, 2002;Hwang et al, 2004Hwang et al, , 2005Ishibashi, 1993;Kaku and Asakusa, 1991;Sirkelis, 2005, 2008;Kitayama et al, 1991;Kuang and Wong, 2006;Le-Trung et al, 2010;Lee et al, 2010;Leon, 1990;Liu, 2006;Lu et al, 2012;Megget, 1974;Meinheit and Jirsa, 1977;Morita et al, 1999;Murty et al, 2003;Noguchi and Kashiwazaki, 1992;Noguchi and Kurusu, 1988;Oka and Shiohara, 1992;Otani et al, 1984;Pantelides et al, 2002;Park and Paulay, 1974;Shrestha et al, 2009;...…”
Section: Experimental Databasementioning
confidence: 99%
“…The authors found that both bar slips and FRP debonding were completely controlled with appropriate anchoring systems in the form of steel profiles and plates [10,11]. The seismic performance of shear-deficient joints subjected to both cyclic and monotonic loads was also studied by Shrestha et al [12] who developed an analytical model to estimate the influence of FRP sheets in shear strengthening of RC connections.…”
Section: Introductionmentioning
confidence: 99%
“…It is obvious that confinement increases the performance of RC structures. Many researchers [5,8,10,14] accepted that the increased confinement of joints caused by externally bonded FRP leads to the improvement in the performance of the repaired or strengthened RC beamcolumn connections subjected to cyclic lateral loads. However, in the previous studies, most of the retrofitting techniques were bonding FRP at the joints around square or rectangular sections of the columns and/or beams, which may give little confinement effect.…”
Section: Introductionmentioning
confidence: 99%